Narrative Review: Transformasi Kesehatan Dan Keselamatan Kerja Di Era Digitalisasi Pelayanan Kesehatan - Fithri Handayani Lubis (STIKES Columbia Asia Medan, 2025)
This narrative review aims to explore the transformation of occupational health and safety (OHS) in the era of healthcare digitalization. The background highlights the increasing complexity of hospital services and the urgent need to integrate digital innovation into OHS programs. The method used was a narrative review based on 32 articles published between 2020 and 2025, selected through systematic search in PubMed, Scopus, ScienceDirect, and Google Scholar. The findings indicate that digital health technologies, including wearable devices, electronic incident reporting systems, and mobile applications for infection control, significantly enhance the effectiveness of OHS by improving compliance, strengthening safety culture, and reducing hospital-acquired infections and adverse events. Nevertheless, challenges remain regarding infrastructure readiness, digital literacy, and data security. The implications of this study suggest that hospitals and policymakers should consider digital-based OHS strategies as an integral part of patient safety improvement and quality health services.